An optimized isolation protocol yields high‐quality RNA from cassava tissues (Manihot esculenta Crantz). Issue 4 (20th February 2019) - Behnam, Babak; Bohorquez‐Chaux, Adriana; Castaneda‐Mendez, Oscar Fernando; Tsuji, Hiroyuki; Ishitani, Manabu; Becerra Lopez‐Lavalle, Luis Augusto
Abstract : We developed and modified a precise, rapid, and reproducible protocol isolating high‐quality RNA from tissues of multiple varieties of cassava plants ( Manihot esculenta Crantz). The resulting method is suitable for use in mini, midi, and maxi preparations and rapidly achieves high total RNA yields (170–600 μg·g −1 ) using low‐cost chemicals and consumables and with minimal contamination from polysaccharides, polyphenols, proteins, and other secondary metabolites. In particular, A 260  :  A 280 ratios were > 2.0 for RNA from various tissues, and all of the present RNA samples yielded ribosomal integrity number values of greater than six. The resulting high purity and quality of isolated RNA will facilitate downstream applications (quantitative reverse transcriptase‐polymerase chain reaction or RNA sequencing) in cassava molecular breeding. Abstract : The modified protocol presented here provides high‐quality RNA from different cassava tissues with a good balance between cost and efficiency and may facilitate gene expression studies in cassava molecular breeding programs.